Dimensions of contemporary Sanskrit research - Panse, Ujjwala 1959-2022; Jha, Vashishtha N. 1946-; Mishra, Arun Ranjan (Delhi, India New Bharatiya Book, 2008)
Festschrift volume to Vashishtha Narayan Jha, b. 1946, Indologist from West Bengal; comprises contributed papers on various aspects of Vedic literature and philosophy
Includes bibliographical references. - English and Sanskrit
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Vedic literature -- History and criticism; Hindu Philosophy; Aufsatzsammlung; Festschrift